Visiting the hyporheic zone: young Atlantic salmon move through the substratum. (8th May 2013) - Heggenes, Jan; Bremset, Gunnbjørn; Brabrand, Åge
Summary: The hyporheic zone may be a habitat for fish, depending on habitat patch characteristics and interactions with fish behaviour, such as movements. Theory highlights the vertical connection and potentially significant functional role of the hyporheic zone, but actual use of the hyporheic zone by fish is understudied. In replicated factorial field experiments, we investigated movements of (i) young Atlantic salmon of various size ( Salmo salar, mean total lengths, 28.3, 51.7, 52.1 and 84.6 mm) through substrata of (ii) different particle size (16–22, 24–60 mm) and (iii) thickness (20, 40, 60 cm), depending on (iv) current direction (horizontal up‐ to downstream, vertical 'upwelling') and (v) temperature/season (summer/autumn). In nine experiments, each with different treatments, three replicated 14‐cm‐diameter translucent PVC tubes were used as a proxy for the hyporheic zone and placed in parallel on the bottom in a natural salmon stream. Each tube consisted of five separable 20‐cm segments, with a no‐substratum segment in each end and three midsegments filled with substratum. Young salmon were placed in the upstream or/and downstream free segment, localised by a snorkeler every 15 min, and after 135 min, the segments were separated and the fish per segment counted. Results indicated that (i) a significant number of fish moved into the substratum, (ii) small Atlantic salmon (28 mm) in June rapidly moved into, and even 60 cm through, both substratum particle sizes regardless of flow direction, but fewer fish into the fine substratum, and (iii) significant numbers of larger fish (52 mm, 85 mm) in September and November also moved into the 24–60 mm substratum, but not so far and relatively fewer remained in the substratum. Horizontal or vertical flow did not affect results. We conclude that young Atlantic salmon can easily move into and through the interstitial spaces in the substratum, depending on fish size and substratum coarseness. The active use by Atlantic salmon of the substratum as part of their habitat remains to be studied, but is likely to be more prevalent than commonly assumed.